PENGARUH GAYA KEPEMIMPINAN TRANSAKSIONAL, DISIPLIN KERJA DAN BURNOUT TERHADAP KINERJA KARYAWAN: Studi Empiris pada Karaoke Grand Charly Semarang - Irsal Fauzi; Meida Rachmawati (Journal of Sustainable Business Hub, 2021)
This research was conducted with the aim of: 1) analyzing the influence of transactional leadership on the performance of Grand Charly Karaoke employees, 2) analyzing the effect of work discipline on the performance of Grand Charly Karaoke employees, 3) analyzing the effect of burnout on the performance of Grand Charly Karaoke employees. This study uses primary data and secondary data. The study population was 35 employees of the Grand Charly Karaoke employees at September 2021. The sample was 35 people’s using the sensus method. Collecting data through: observation, interviews, questionnaires and documentation. The analytical method used is multiple linear regression analysis with the SPSS programs version 23. The results of the study prove that simultaneously the transactional leadership, work discipline and burnout variables have a positive and significant effect on the performance of Grand Charly Karaoke employees with an F-count 46.638 with sig = 0.00. Partially the work discipline variable has a dominant influence compared to other variables with the t value of 2.960. Keywords: Transactional leadership, Work Discipline, Burnout and Employee Performance